A Matter of Perception - Roosz, Bernard de (Student Undergraduate Research E-journal!, 2019)
This pilot study explores the possibility of cognitive training software Neurotracker (NT), to have potential beneficial effects for Traumatic Brain Injury patients with Sensory Processing Disorder. Five subjects with TBI and SPD trained for 5 weeks/21 sessions with Neurotracker. Pre-post training cognitive tests (WAIS TMTA, TMTB, LNS) and surveys were conducted to measure possible cognitive differences with no statistical significant results. However, significant improvement in Neurotracker scores were found. (α=.05, P=.043) between T1 (M=1.79, SD=0.44) and T2 (M =2.73, SD = 0.55) and positive changes associated with attention attention span, divided attention, (multiple) object tracking and motion sickness.